2021
DOI: 10.24843/jchem.2021.v15.i01.p09
|View full text |Cite
|
Sign up to set email alerts
|

BENTONIT-Fe3O4 SEBAGAI FOTOKATALIS DALAM PROSES FOTODEGRADASI NAPHTHOL BLUE BLACK DENGAN IRADIASI UV

Abstract: Bentonit adalah salah satu jenis bahan yang umum.digunakan sebagai penyerap limbah zat warna. Namun, terdapat kesulitan dalam pemisahan dan pengumpulan kembali..adsorben setelah proses penyerapan. Oleh karena itu, dalam penelitian ini bentonit dijadikan komposit dengan oksida besi yang bersifat magnetik untuk mengatasi masalah tersebut.  Penelitian ini bertujuan untuk mendegradasi zat warna Napthol blue black  menggunakan bentonit-Fe3O4 bukan sekedar adsorben melainkan sebagai fotokatalis.. Penelitian ini.meli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…Based on Figure 3(a), bentonite particles have uniform morphologies, such as spherical, large flakes, layered structures [9], and irregular particle surfaces. These results are the same as those of previous research conducted by Suprihatin et al [6]. After modification with the TiO2 species shown in Figures 3(b) and 3(c), the bentonite surface changed, producing some small particles with a layered structure.…”
Section: Scanning Electron Microscopy-energy Dispersive X-ray (Sem-edx)supporting
confidence: 91%
See 4 more Smart Citations
“…Based on Figure 3(a), bentonite particles have uniform morphologies, such as spherical, large flakes, layered structures [9], and irregular particle surfaces. These results are the same as those of previous research conducted by Suprihatin et al [6]. After modification with the TiO2 species shown in Figures 3(b) and 3(c), the bentonite surface changed, producing some small particles with a layered structure.…”
Section: Scanning Electron Microscopy-energy Dispersive X-ray (Sem-edx)supporting
confidence: 91%
“…This phenomenon causes methylene blue to be adsorbed more effectively at acidic than alkaline pH. From the test results on ten catalysts, it can be concluded that the BT-10%, BT-20%, BT-30%, BT-40%, BT-50%, BT-60%, BT-70%, BT-80%, BT-90%, and BT-100% are active at an acidic pH of 1 [6].…”
Section: Effect Of Ph Variationmentioning
confidence: 98%
See 3 more Smart Citations